Роль α-токоферола и N-ацетил-L-цистеина в оксидативном стрессе, индуцированном менадионом - Донченко, Г.В.; Петрова, Г.В. (Видавничий дім "Академперіодика" НАН України, 2008)
It is established that α-tocopherol does not play the main role in the protection of rat thymo-cytes from damaging by menadione - generated superoxide that calls into question its ability to prevent oxidative stress. Efficiency of a predecessor of the glutatione synthesis, N-acetyl-L-cysteine, in the given model testifies to involving other antioxidative protection systems in this process.